CHARACTERISTICS OF TURBULENT FLOW (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
Turbulent flow is a complex and chaotic movement of fluid that occurs when a fluid moves at high velocities or interacts with solid boundaries. This phenomenon is critical in a wide range of scientific and engineering applications, such as in weather systems, industrial processes, and aerodynamics. This paper aims to explore the fundamental characteristics of turbulent flow, including its underlying mechanisms, mathematical descriptions, and practical implications. The study also delves into the transition from laminar to turbulent flow, key parameters like the Reynolds number, and turbulence modeling techniques.